Chemical Weathering and Mineralogy of McMurdo Dry Valley Streams: Examining the Controls of Current and Future Ephemeral Stream Geochemistry - Scheuermann, Jordan (The Ohio State University, 2015)
The McMurdo Dry Valleys form the largest ice-free region in Antarctica and are the coldest, driest deserts in the world. But, for approximately 6-12 weeks per year in the austral summer, continuous sunlight and near-freezing temperatures create meltwater streams that descend from the surrounding alpine glaciers. These ephemeral streams are a distinctive feature in the barren dry valley landscape and are important sources of nutrients and solutes from the weathering of streambed and hyporheic zone materials. This setting has been a US National Science Foundation funded Long-Term Ecological Research (LTER) project since 1993. A major goal of the McMurdo LTER is to understand how liquid water, the primary limiting condition for life in Antarctica, is affected by climate variability. The McMurdo Dry Valleys are extremely climate-sensitive and even seemingly small variations in temperature can have a drastic effect on hydrological activity. The McMurdo LTER program has been successful in collecting and analyzing a large amount of stream data pertaining to weathering products but, a more comprehensive analysis and interpretation of the data have yet to be undertaken. Assessment of current and future stream geochemistry is critical to predict the impact of increased water flow due to glacier melt and increasing temperature which could greatly influence the ecological function and biologic diversity in the McMurdo Dry Valleys. Surface sediments were collected at multiple locations from ephemeral streams and analyzed using a scanning electron microscope and x-ray diffraction to determine sediment mineralogy and evidence of chemical weathering. Geochemical reactions were modeled using previously collected stream water data and the USGS PHREEQC software for the speciation calculations and the assessment of the solubility controlling solid phases. Chemical weathering was apparent through visible mineral alteration and the formation of secondary weathering products. Modeling results indicate that stream geochemistry will not significantly be affected by increased water temperature in the future. These results suggest stream geochemistry and chemical weathering may instead be controlled primarily through hydrologic exchange in the hyporheic zone. Shell Exploration and Production Company National Science Foundation No embargo Academic Major: Earth Sciences